Rapid scale-up of COVID-19 training for frontline health workers in 11 African countries - Fatima Tsiouris; Kieran Hartsough; Michelle Poimbouef; Claire Raether; Mansoor Farahani; Thais Ferreira; Collins Kamanzi; Joana Maria; Majoric Nshimirimana; Job Mwanza; Amon Njenga; Doris Odera; et al. (BMC, 2022)
Abstract Background The global spread of the SARS-CoV-2 virus highlights both the importance of frontline healthcare workers (HCW) in pandemic response and their heightened vulnerability during infectious disease outbreaks. Adequate preparation, including the development of human resources for health (HRH) is essential to an effective response. ICAP at Columbia University (ICAP) partnered with Resolve to Save Lives and MOHs to design an emergency training initiative for frontline HCW in 11 African countries, using a competency-based backward-design approach and tailoring training delivery and health facility selection based on country context, location and known COVID-19 community transmission. Methods Pre- and post-test assessments were conducted on participants completing the COVID-19 training. Parametric and non-parametric methods were used to examine average individual-level changes from pre- to post-test, and compare performance between countries, cadres, sex and facility types. A post-evaluation online training survey using Qualtrics was distributed to assess participants' satisfaction and explore training relevance and impact on their ability to address COVID-19 in their facilities and communities. Results A total of 8797 HCW at 945 health facilities were trained between June 2020 and October 2020. Training duration ranged from 1 to 8 days (median: 3 days) and consisted of in person, virtual or self guided training. Of the 8105 (92%) HCW working at health facilities, the majority (62%) worked at secondary level facilities as these were the HF targeted for COVID-19 patients. Paired pre- and post-test results were available for 2370 (25%) trainees, and 1768 (18%) participants completed the post-evaluation training survey. On average, participants increased their pre- to post-test scores by 15 percentage points (95% CI 0.14, 0.15). While confidence in their ability to manage COVID-19 was high following the training, respondents reported that lack of access to testing kits (55%) and PPE (50%), limited space in the facility to isolate patients (45%), and understaffing (39%) were major barriers. Conclusion Ongoing investment in health systems and focused attention to health workforce capacity building is critical to outbreak response. Successful implementation of an emergency response training such as this short-term IPC training initiative in response to the COVID-19 pandemic, requires speed, rigor and flexibility of its design and delivery while building on pre-existing systems, resources, and partnerships.